Manufacturing of Wear Resistant Iron-Steel: A Theoretical and Experimental Research on Wear Behavior - Bildik, O.; Yaşar, M. (Engineering, Technology & Applied Science Research, 2021)
In this study, four different alloys of steel blocks with a thickness of 15mm were manufactured in order to develop an alternative to steel plates used in wear exposed areas of construction machines, trucks, and asphalt production plants. To further increase the wear resistance of the manufactured steel blocks, their thickness was reduced to 10mm by the hot-rolling method. Wear specimens were obtained from rolled blocks. These specimens were abraded at 20N, 40N, and 60N loads in reciprocating linear motion module ASTM G-33 standards to determine their wear resistance. SEM and EDX analyses were also conducted to see modifications on the worn surfaces. In addition, a theoretical model of wear behaviors was created, calculations were made with Archard wear equation and ANSYS software, and the theoretical and experimental results were compared